2019
DOI: 10.1088/1742-6596/1279/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins B therapy in Regeneration of Peripheral Neuropathy Associated with Lipid Profile

Abstract: Objective: To investigate the role of serum lipid profile during the regeneration of experimental crush peripheral nerve injury to rats. Besides, to investigate which type of vitamin B therapy is better to accelerate the regeneration processes.Methods: Seventy-five male albino rats male, aged between 10 to 12 weeks were equally divided into 5 treated groups: B1, B6, B12, Tri-B complex and normal saline. Rats of therapeutic groups were administered according to the grouping and lasted to 45 consecutive days, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The deficiency of vitamin B12 can result in neurotoxicity and contribute to the development of subacute combined degeneration, a disorder of the CNS characterized by sensory deficits, motor weakness, paresthesia, and gait ataxia [ 79 ]. In addition, within the peripheral nervous system, there is evidence suggesting that B vitamins play a role in peripheral nerve repair following insult [ 80 ]. Four studies investigated the role of vitamin B12 after PNI using rat models; two used vitamin B12 in combination with other vitamins [ 81 , 82 ], and two investigated the role of vitamin B12 alone [ 80 , 83 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The deficiency of vitamin B12 can result in neurotoxicity and contribute to the development of subacute combined degeneration, a disorder of the CNS characterized by sensory deficits, motor weakness, paresthesia, and gait ataxia [ 79 ]. In addition, within the peripheral nervous system, there is evidence suggesting that B vitamins play a role in peripheral nerve repair following insult [ 80 ]. Four studies investigated the role of vitamin B12 after PNI using rat models; two used vitamin B12 in combination with other vitamins [ 81 , 82 ], and two investigated the role of vitamin B12 alone [ 80 , 83 ].…”
Section: Reviewmentioning
confidence: 99%
“…In addition, within the peripheral nervous system, there is evidence suggesting that B vitamins play a role in peripheral nerve repair following insult [ 80 ]. Four studies investigated the role of vitamin B12 after PNI using rat models; two used vitamin B12 in combination with other vitamins [ 81 , 82 ], and two investigated the role of vitamin B12 alone [ 80 , 83 ]. Combined B-vitamin administration improved the toe-spreading reflex [ 81 ].…”
Section: Reviewmentioning
confidence: 99%
“…In addition, accelerated nerve regeneration by the combination of vitamins B1, B6, and B12 was suggested from other studies [63,64] which, however, were too small to show significant results. A recently published study investigated the effect of vitamin B therapy in the regeneration of experimental crush peripheral nerve injury to rats and appeared to contradict this finding and attributed vitamin B12 alone or in combination with B1 and B6 a stronger nerve-regenerating effect than vitamin B1 or B6 alone [65]. However, while the authors specified the doses of the individually administered vitamins (B1/B6/B12 180/180/1 mg/kg/day), they did not break it down for the combination (described as a total dose of 20 mg/kg/day).…”
Section: Yesmentioning
confidence: 99%
“…Al-Saaeed et al evaluated the rate of peripheral nerve regeneration in response to daily intramuscularly injection of different B vitamins (B1, B6, and B12). They found an increase in the number and density of regenerated myelinated fibers in the vitamin B-treated groups, in particular after treatment with vitamin B12, which was followed by vitamin B1 and vitamin B6 treatment [69,129]. A study by Ehmedah et al demonstrated a modulatory effect on the macrophage-SC interaction during the early stages of Wallerian degeneration after nerve injury.…”
Section: Water-soluble Vitamins Vitamin Bmentioning
confidence: 99%
“…Cobalamin is usually consumed in the form of the co-enzyme de-oxadenosylcobalamin or methylcobalamin. Several studies have highlighted a positive effect of methylcobalamin and vitamin B12 on the myelination process by increasing the expression of myelin basic protein in SCs [147], thus accelerating the myelination process [69,129]. Furthermore, when administered together with dexamethasone (an anti-inflammatory glucocorticoid often prescribed after peripheral nerve injury) after traumatic sciatic nerve injury in rats, vitamin B12 increases the number of SCs and myelinated nerve fibers as well as the diameter of regenerating axons.…”
Section: Water-soluble Vitamins Vitamin Bmentioning
confidence: 99%